You can't always say what you want the paradox of free speech - Baron, Dennis 1944- (Cambridge University Press, 2023)
The freedom to think what you want and to say what you think has always generated a pushback of regulation and censorship. This raises the thorny question: to what extent does free speech actually endanger speech protection? This book examines today's calls for speech legislation and places it into historical perspective, using fascinating examples from the past 200 years, to explain the historical context of laws regulating speech. Over time, the freedom to speak has grown, the ways in which we communicate have evolved due to technology, and our ideas about speech protection have been challenged as a result. Now more than ever, we are living in a free speech paradox: powerful speakers weaponize their rights in order to silence those less-powerful speakers who oppose them. By understanding how this situation has developed, we can stand up to these threats to the freedom of speech